STUDI PENYALURAN KREDIT BANK UMUM SWASTA NASIONAL DI INDONESIA PERIODE 2011-2015 - Khibtiyah, 13.05.51.0192; Masdjojo, Gregorius N. (Students' Journal of Economic and Management, 2017)
This study aims to examine and analyze the influence of Saving, Capital Adequacy Ratio, Non Performing Loans, Return On Assets and Interest Rate on National Private Commercial Bank loan on the period 2011-2015. The population in this study is a national private commercial bank which are operating in Indonesia from 2011 until 2015. The samples are determined using purposive sampling technique. Data analysis was performed using panel data regression with selection between Fixed Effect Model (FEM) and the Random Effects Model (REM) through the Hausman test. Hausman test result recommends using FEM. Based on the output FEM showed that the Saving has a significant positive effect on Bank Loan, Capital Adequacy Ratio has no effect on Bank Loan, Non Performing Loans has no effect on Bank Loan, Return On Assets has no effect on Bank Loan and Interest has significant negative effect on Bank Loan. Keywords: Third Party Funds, Capital Adequacy Ratio, Non Performing Loans, Return On Assets, Interest Rate, Credit, Fixed Effect Model (FEM) And The Random Effects Model (REM).